A Rare case of recurrent Guillain-Barré syndrome without albuminocytological dissociation - Yelam, Anudeep (BMJ Case Rep, 2018)
Guillain-Barré syndrome (GBS) is an immune-mediated polyneuropathy, often preceded by an illness. It is a self-limiting illness in most of the cases, but recurrence is rare and can be seen in about 1%–6% of patients. GBS is characterised by progressive, symmetrical, proximal and distal weakness. Areflexia and sensory disturbances are also common. Patients with GBS usually have albuminocytological dissociation on cerebrospinal fluid (CSF) analysis. This is a case of a 69-year-old woman with recurrent GBS and normal CSF findings.